Unveiling Talaromyces marneffei emergence among HIV/AIDS patients: exploring phylogeny and molecular identification: T. marneffei Emergence among HIV/AIDS Patients - Mezher , Milad A.; Al Hosiny , Ibrahim M.; Al-Joufi , Fakhria A.; Alenazy , Rawaf; Alzahrani , Hayat Ali; Selim , Heba Mohammed Refat M.; Mansour, Ahd A.; Elnoamany , Fagelnour; Salem-Bekhit, Mounir M. (Cellular and Molecular Biology, 2025)
Talaromyces marneffei is a pathogenic fungus that causes fatal health complications for patients who are infected with HIV. For the current investigation, sputum samples were collected from 19 immunosuppressed patients from two hospitals located in Baghdad, Iraq by which they were inoculated onto both Sabouraud dextrose agar (SDA) medium at 25 °C and BHI (brain heart infusion) agar at 36±1 °C for growth before being identified using single and nested PCR methods. The 18S rRNA gene sequence of T. marneffei was used to create two sets of oligonucleotide primers, RRF1 and RRH1 which are considered fungus-specific outer primers were employed. Both nested and solo PCRs using the T. marneffei-specific inner primers (Pm1 and Pm2) were carried out. To define the phylogenetic relatedness of this isolate, the MEGA X program was used to align the nuclear ribosomal DNA (rDNA) sequences of T. marneffei. Results showed that the wine-colored pigmented isolates in agar were dimorphic, exhibited bloom-like twigs and spore chains characteristic under the microscope, and were filamentous type colonies with light yellow villi. Finally, immuno-compromised patients in Iraq have T. marneffei in their blood cultures that will be induced to pathogenicity, and the PCR assay is valuable for T. marneffe identifying. Other results from nested PCR revealed that 8 human isolates, from 19, have specific fragments of about 400 bp on the agarose gel.